Learning Obstacles and Students' Difficulties in Solving the Problem of Pythagorean Theorem: A Systematic Literature Review - Bariyah, Nusrotul; Prabawanto, Sufyani; Dahlan, Jarnawi Afgani (FKIP Universitas Lampung, 2024)
Pythagorean's theorem is a fundamental concept in mathematics that is widely used in various fields, including geometry, physics, and engineering. The ability to understand and apply these theorems is important in solving geometric problems and calculating distances or angles in real contexts. However, there are learning obstacles and difficulties for students in solving the problems of the Pythagorean theorem. This study aims to describe the learning obstacles and difficulties of students in solving Pythagorean theorem material through Systemic Literature Review (SLR). The article search strategy applies inclusion and exclusion criteria. The selection process was 19 selected articles using CASP checklist with articles coming from Google Scholar, Scopus, Springer Link, IEEE Explore, and PubMed databases. Based on the results of the study, it was obtained that students' learning obstacles came from epistemological obstacles, ontogenic obstacles, and didactical obstacles. The students' difficulties are dominated by conceptual difficulties. Learning obstacles cause learning difficulties. Studying students' learning obstacles and difficulties can assist a teacher identify student learning problems. Keywords: learning difficulties, learning obstacles, pythagorean theorem, systematic literature review.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1939-1960